Tracking of Host Defenses and Phylogeny During the Radiation of Neotropical Inga-Feeding Sawflies (Hymenoptera; Argidae) - Endara, María-José; Nicholls, James A.; Coley, Phyllis D.; Forrister, Dale L.; Younkin, Gordon C.; Dexter, Kyle G.; Kidner, Catherine A.; Pennington, R. T.; Stone, Graham N.; Kursar, Thomas A. (Frontiers in Plant Science, 2018)
Coevolutionary theory has long predicted that the arms race between plants and herbivores is a major driver of host selection and diversification. At a local scale, plant defenses contribute significantly to the structure of herbivore assemblages and the high alpha diversity of plants in tropical rain forests. However, the general importance of plant defenses in host associations and divergence at regional scales, remains unclear. Here, we examine the role of plant defensive traits and phylogeny in the evolution of host range and species divergence in leaf-feeding sawflies of the family Argidae associated with the Neotropical genus of trees Inga throughout the Amazon, the Guiana Shield and Panama. Our analyses show that the phylogenies of both the sawfly herbivores and their Inga hosts are congruent, and that sawflies radiated approximately the same time, or more recently than their Inga hosts. Analyses controlling for phylogenetic effects show that the evolution of host use in the sawflies associated with Inga is better correlated with Inga chemistry than with Inga phylogeny, suggesting a pattern of delayed host defense tracking closely tied to host chemistry. Finally, phylogenetic analyses show that sister species of Inga-sawflies are dispersed across the Neotropics, suggesting a role for allopatric divergence and vicariance in Inga diversification. These results are consistent with the idea that host defensive traits play a key role not only in structuring the herbivore assemblages at a single site, but also in the processes shaping host association and species divergence at a regional scale.